2018
DOI: 10.1002/rev3.3149
|View full text |Cite
|
Sign up to set email alerts
|

School‐based interventions for attention‐deficit/hyperactivity disorder: A systematic review with multiple synthesis methods

Abstract: Non‐pharmacological interventions for attention‐deficit/hyperactivity disorder are useful treatments, but it is unclear how effective school‐based interventions are for a range of outcomes and which features of interventions are most effective. This paper systematically reviews randomised controlled trial evidence of the effectiveness of interventions for children with ADHD in school settings. Three methods of synthesis were used to explore the effectiveness of interventions, whether certain types of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 104 publications
(295 reference statements)
1
30
0
Order By: Relevance
“…Therefore, our findings suggest that support for teachers to help focus attention and manage associated behavioural disturbance is a priority. For example, a recent multi-method systematic review reported tentative evidence for daily report cards to improve consistent communication between home and school for children with ADHD (Moore et al, 2018). The associated qualitative comparative analysis suggested that strategies that improve self-regulation and are delivered one-to-one were commonly among the most effective interventions for academic outcomes, particularly if combined with personalized programmes and delivered in the classroom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our findings suggest that support for teachers to help focus attention and manage associated behavioural disturbance is a priority. For example, a recent multi-method systematic review reported tentative evidence for daily report cards to improve consistent communication between home and school for children with ADHD (Moore et al, 2018). The associated qualitative comparative analysis suggested that strategies that improve self-regulation and are delivered one-to-one were commonly among the most effective interventions for academic outcomes, particularly if combined with personalized programmes and delivered in the classroom.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of interventions for children with ADHD in school settings demonstrate that interventions focusing on academic skills to improve academic outcomes tend to be trialled and presumably intended for older children than those in our sample (Moore et al, 2018). Therefore, early intervention that targets the attainment gap for young children with ADHD symptoms should be encouraged.…”
Section: Future Researchmentioning
confidence: 99%
“…This decision may have some consequences as the combination of stand-alone interventions represented in the first row of Tables 2, 3, and 4 do not necessarily represent planned combinations of treatment in multimodal interventions. Indeed, another meta-analysis has indicated greater effect size magnitudes for planned combinations of treatments (Moore et al, 2018), and combined treatment is widely recommended for ADHD (Barbaresi et al, 2020). Planned companion papers will further investigate the role of these psychosocial combinations in a network meta-analysis (Schatz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that we work toward creating cross-level research that makes connections and validates the relationships between conceptual and empirical models at the different levels (Moore et al, 2018; Musso et al, 2019; Sánchez et al, 2019). Only in this way can we verify the external validity of each construct, not only between constructs at the same level, but also between constructs in different research levels and domains.…”
Section: Discussionmentioning
confidence: 99%